Agents of innovation : entrepreneurs, facilitators and intrapreneurs - Filion, Louis Jacques (Emerald Publishing Limited, 2023)
What does it mean to innovate? What skills are needed? What thought processes are involved? Answers to these questions can be found in the real-life stories of Agents of Innovation. Louis Jacques Filion and chapter co-authors Rico J. Baldegger, Candido Borges, Fernando Dolabela, Joëlle Hafsi and Francine Richer, present six fascinating case histories of three different types of agents of innovation: entrepreneurs, who create new products or services, facilitators, or process innovators, who help entrepreneurs to develop their enterprises, and intrapreneurs, who innovate within the organizations that employ them. In the second part of Agents of Innovation, a set of exercises guide readers as they develop their own innovative thinking process. Valuable to researchers, students, and those about to branch out into the world of business, Agents of Innovation informs many different disciplines, and in particular strategy - the sister discipline of entrepreneurship as far as the implementation of innovation is concerned.
Includes index.
Keywords: Chanel (Firm); Clothing trade -- Technological innovations.; Technological innovations.; Entrepreneurship.; Business & Economics -- Entrepreneurship.; elektronické knihy; electronic books